The propagation of business sentiment within the European Union? - Anja Kukuvec; Harald Oberhofer (Austrian Institute of Economic Research (WIFO), 2018)
This paper empirically investigates the propagation of business sentiment within the EU and adds to the literature on shock absorption via a common market's real economy. To this end, we combine EU-wide official business sentiment indicators with world input-output data and information on indirect wage costs. Econometrically, we model interdependencies in economic activities via input-output linkages and apply space-time models. The resulting evidence provides indication for the existence of substantial spillovers in business sentiment formation. Accordingly, and highlighted by the estimated impacts of changes in indirect labour costs, policy reforms aiming at increasing the resilience of the European single market need to take these spillovers into account in order to increase its effectiveness.
Keywords: C33; D84; E32; J32; L14; 330; Business sentiment; propagation; economic fluctuations; input-output linkages; networks; space-time model; policy reforms